A Pilot Study on Playback Theatre as a Therapeutic Aid after Natural Disasters: Brain Connectivity Mechanisms of Effects on Anxiety. (October 2020) - Munjuluri, Sarat; Bolin, Peter K.; Amy Lin, Y. T.; Garcia, Nina L.; Gauna, Leslie; Nguyen, Tien; Salas, Ramiro
Background: Natural disasters can affect mental health and result in symptoms of depression, anxiety, and post-traumatic stress disorder (PTSD). Playback Theatre (PT) is a form of improvisation where actors play-back personal stories told by audience members. Whether PT can be therapeutic in post-disaster settings is not known. Method: We used a series of PT performances and studied levels of depression, anxiety, and PTSD symptoms in a sample of 13 people affected by Hurricane Harvey that happened in Houston, TX, August 2017. Brain imaging, specifically resting state functional connectivity of the amygdala was also studied before and after the PT performances. Results: Both anxiety ( p  = .001, Cohen's d = –1.25) and PTSD ( p  = .002, Cohen's d = –1.0) symptoms significantly decreased after a series of 4 PT performances from January 2019 – February 2019. Depression reduction was not significant. We performed resting state functional connectivity (RSFC) MRI before and after the series of performances. We used the right and left amygdala as seeds for RSFC analysis and found that the connectivity between the left amygdala and the bilateral supramarginal gyri was increased after PT. The bilateral supramarginal connectivity with the default mode and the saliency networks increased too, which correlated with reduction in anxiety scores. Conclusions: PT may offer a form of intervention for anxiety caused by disasters. An increase in left amygdala/supramarginal gyri connectivity may be the underlying mechanism.